Multifactorial T cell Hypofunction that is Reversible Can Limit the Efficacy of Chimeric Antibody Receptor-transduced Human T cells in Solid Tumors - Moon, Edmund K. (2014)
PURPOSE: Immunotherapy using vaccines or adoptively transferred tumor infiltrating lymphocytes (TILs) is limited by T cell functional inactivation within the solid tumor microenvironment. The purpose of this study was to determine if a similar tumor-induced inhibition occurred with genetically-modified cytotoxic T cells expressing chimeric antibody receptors (CARs) targeting tumor-associated-antigens. METHODS: Human T cells expressing CAR targeting mesothelin or fibroblast activation protein and containing CD3ζ and 4-1BB cytoplasmic domains were intravenously injected into immunodeficient mice bearing large, established human mesothelin- expressing flank tumors. CAR TILs were isolated from tumors at various time points and evaluated for effector functions and status of inhibitory pathways. RESULTS: CAR T cells were able to traffic into tumors with varying efficiency and proliferate. They were able to slow tumor growth, but did not cause regressions or cures. The CAR TILs underwent rapid loss of functional activity that limited their therapeutic efficacy. This hypofunction was reversible when the T cells were isolated away from the tumor. The cause of the hypofunction appeared to be multifactorial and was associated with upregulation of intrinsic T cell inhibitory enzymes (diacylglycerol kinase and SHP-1) and the expression of surface inhibitory receptors (PD-1, LAG3, TIM3, 2B4). CONCLUSIONS: Advanced generation human CAR T cells are reversibly inactivated within the solid tumor microenvironment of some tumors by multiple mechanisms. The model described here will be an important tool for testing T cell-based strategies or systemic approaches to overcome this tumor-induced inhibition. Our results suggest that PD-1 pathway antagonism may augment human CAR T cell function.